Dietary vitamin E and lipid and color stability of beef and pork: modeling of relationships - Sales, J; Koukolová, V (Journal of animal science, 2011)
Dietary vitamin E supplementation provides a feasible option to extend the shelf life of meat. However, the costs of extra supplementation necessitate an accurate level of feeding to achieve the maximum return in product quality improvement. The current study aimed to quantify the effects of total dietary vitamin E intake on muscle α-tocopherol concentration in cattle and pigs, and to relate muscle α-tocopherol concentration to lipid oxidation and color of meat. Through computerized and manual searches, 13 studies with cattle and 10 with pigs were identified that have presented data on dietary vitamin E intake and muscle α-tocopherol concentration. Treatment means from 12 studies with beef and 14 with pork were used to evaluate the effects of muscle α-tocopherol concentration on lipid oxidation, as represented by thiobarbituric acid reactive substances in meat stored or retail displayed at chilled temperatures. With CIELAB a* (redness) values as an indicator of color development, the association between muscle α-tocopherol concentration and color could be evaluated with treatment means from 8 studies with beef and 5 with pork. Different treatments applied within studies resulted in 20 to 66 values available for the respective regression analyses. Relationships could be described effectively by different forms of the Mitscherlich model, which presented an initial value for y when x = 0, an asymptotic plateau, and the rate of change of y with increasing values of x. With the inclusion of experiment as a random effect, the relationship between total dietary vitamin E intake (x, IU/d for cattle and mg/d for pigs) and muscle α-tocopherol concentration (y, µg/g of meat) reached asymptotic plateau values at 5.71 and 4.83 µg/g of meat for cattle and pigs, respectively. The fractional accumulation rate (per total dietary vitamin E intake) of muscle α-tocopherol concentration was considerably greater in pigs (0.0130) than in cattle (0.00174). The form of the relationship between muscle α-tocopherol concentration and thiobarbituric acid reactive substances in pork was influenced by a single value, whereas muscle α-tocopherol concentrations could not be related to a* values in beef. This study presented viable models that could be applied in practice to calculate the amounts of supplemental dietary vitamin E needed to obtain the maximum profit from beef and pork.
Keywords: alfa-tokoferol; Vitamin E; Color; peroxidace lipidů; lipidy; zvířata; Meat; Swine; kosterní svaly; Cattle; prasata; Muscle, Skeletal; barva; skot; maso; Lipids; Dietary Supplements; potravní doplňky; alpha-Tocopherol; Animals; vitamin E; Lipid Peroxidation